Transposon-mediated generation of targeting vectors for the production of gene knockouts - Zhang, Chunfang (Oxford University Press, 2005)
Vectors used for gene targeting experiments usually consist of a selectable marker flanked by two regions of homology to the targeted gene. In a homologous recombination event, the selectable marker replaces an essential element of the target gene rendering it inactive. Other applications of gene targeting technology include gene replacement (knockins) and conditional vectors which allow for the generation of inducible or tissue-specific gene-targeting events. The assembly of gene-targeting vectors is generally a laborious process requiring considerable technical skill. The procedures presented here report the application of transposons as tools for the construction of targeting vectors. Two mini-Mu transposons were sequentially inserted by in vitro transposition at each side of the region targeted for deletion. One such transposon carries an antibiotic resistance marker suitable for selection in mammalian cells. A deletion is then generated between the two transposons either by LoxP-induced recombination or by restriction digestion followed by ligation. This deletion removes part of both transposons plus the targeted region in between, leaving a transposon carrying the selectable marker flanked by two arms which are homologous to the targeted gene. Targeting vectors constructed using these transposons were electroporated into embryonic stem cells and shown to be effective in gene-targeting events.